Effects of diet and abiotic factors on the survival and reproduction of cyclopoid copepod Apocyclops dengizicus / Nur Farahin Mohd Isa - Nur Farahin , Mohd Isa (2019)
Copepods are one of the essential live feeds in aquaculture and are traditionally raised on algal diets. However, sustainable copepod productions in captivity are still unachievable due to lack of cost-effective feed and culture protocols. Hence, this present study investigated the effects of (1) a biotic factor i.e. marine microheterotrophs (bacteria, yeasts and protists) grown in palm oil mill effluent (POME) and (2) abiotic factors i.e. temperature, salinity, pH, photoperiod and light intensity on survival, reproduction and growth (body size) of brackish water copepod Apocyclops dengizicus at a laboratory scale. The aims of this study were to evaluate the feasibility of POME-grown diets for culturing A. dengizicus and determine the optimal conditions for sustainable production of A. dengizicus. For each experiment, an initial stocking density of fifty copepod nauplii (stage I) with triplicates of each treatment was cultured for twelve days. The scale-up experiment with an initial density of 200 nauplii was then tested on the optimized diet(s) and culture conditions gathered from the initial experiments. Copepods fed on POME-grown Meyerozyma guilliermondii (POME-MG) had higher survival (92.0±7.0% by Day 8) (p < 0.05) and total F2 nauplii production (445.7±55.4) (p < 0.05) compared to copepods fed on other POME-grown diets tested i.e. POME- grown: Shewanella algae (POME-SA), Rhodovulum sulfidophilum (POME-RS), Rhodotorula mucilaginosa (POME-RM), Aurantiochytrium limacinum (POME-AL), a mixed diet of POME-(MG+AL) and an instant microalgae diet of Nannochloropsis oculata (N). There were no significant body length and width differences in A. dengizicus between each diet treatments. The highest survival (58.0±% on Day 6) (p < 0.05) and reproduction (101.3±25.4 nauplii) (p < 0.05) were achieved under 10 ppt salinity. The different levels of temperatures (26-36°C), pH (5-9), photoperiod regimes (24:0, 0:24, and 12:12 h light:dark regime) and light intensities (6.08, 14.85 and 23.65 μmol photons m-2 s-1) did not produce a significant variation in survival, reproduction and growth of A. dengizicus. In a scale-up experiment, A. dengizicus fed on POME-MG had significantly higher (p < 0.05) adult survival rate (88.5±3.9%) on Day 6 as compared to only POME diet (72.7±2.9%). However, there were no significant differences in the total number of F2 nauplii between A. dengizicus fed on POME-MG (212.6±11.3) and only POME (206.6±11.1) throughout the 12-day culture period. The nutritional composition of POME-MG diet consisted of 41.8% protein, 11.0% lipids and 24.8% carbohydrates on dry weight basis. It is rich in polyunsaturated fatty acids (8.0%) and essential amino acids (47.2%). As a conclusion, POME-MG is suitable for culturing A. dengizicus with incorporating the optimal culture conditions of 30±1°C, 10±1 ppt, pH 8±0.5, photoperiod regime of 12 hours light and 12 hours dark under low light intensity of 6.08 μmol photons m-2 s-1. This study has shown POME grown microhetetrophs as potential feed for mass culturing copepods.